Revealing the Concept of Adaptive Islamic Education Learning with Cognitive Development in SD Negeri Ulee Kareung - Khairiyanti (Jurnal Profesi Guru Indonesia, 2024)
This article aims to express the concept of learning Islamic religious education in primary schools. In the development of Primary School age children have their own special characteristics, the thinking ability of Primary School age children develops gradually. It needs to be understood wisely to be able to deliver the success of educational goals. This research uses a descriptive qualitative approach with the method of library research (library research). The results of the research show that Islamic religious education in primary schools is quite unique, if in the past children's thinking was still imaginative and egocentric, then now children's thinking is developing towards concrete, rational and objective thinking. The scope of the study of Islamic religious education is the Qur'an, creed, morals, fiqh/worship, and the history of Islamic culture. Educational methods that can be applied refer to the Quranic method, namely the amstal method, the qishah method, the ibrah mauidzah method, the hiwar jadali method, the uswah hasanah method, and the targhib tarhib method. Meanwhile, Islamic religious education can be implemented verbally or non-verbally, written or non-written, aimed at measuring intellectual competence, social competence, social competence and spiritual competence. Thus, Islamic religious education is expected to produce people who always strive to perfect their faith, piety, and morals, and actively build Islamic civilization.